Lecturers’ Perceptions of the Switch from Teaching in the new normal to Normal in a selected university in South Africa - Adu, Kemi Olajumoke; Duku, N (EDUCATIO : Journal of Education, 2023)
The announcement of the lockdown because of the pandemic by the South African President in March 2020 came as a surprise and shock to many academics. Universities in the country have no choice but to switch to virtual classrooms, termed “the new normal” A few months ago, the president of South Africa announced the removal of all restrictions and back to normal conventional classroom face-to-face teaching. The paper investigates the perceptions of the lecturer to ascertain the strategies used to cope and share their experiences. 8 samples were purposively selected in one of the historically disadvantaged universities. A semi-structured interview was used to collect data. The findings revealed among others that virtually all the respondents have adopted one or two coping strategies with diverse experiences. The paper recommended that the lecturers should think outside the box and be 4IR compliance. They should be flexible to adapt to any situation and make use of blended approach pedagogy even while in the normal stage.